Al-kitabah al-jawiyah adatun li Islamiyat al-ma'rifah - Hakim, Amani; Ahmad H.Osman, Rahmah; Mohamad, Amira Hanin; Zainal, Hakim (Al Hikmah Research and Publication Centre., 2022)
The Jawi writing is one of the privileges possessed by Malaysians in general and Muslims in particular, because the Javanese writing is a complete reflection of the Arabic language, as it is similar in writing and letters despite the difference in terms of reading the Arabic language, a language that symbolizes Islamic identity. However, the situation of Jawi writing is increasingly challenged with the introduction of a new writing system based on the Latin script and making people use and prefer it from Jawi script. This leads to a point of concern regarding the mastery of Javanese writing in future generations and their knowledge of reading letters and writings inspired by Arabic letters. Therefore, this study aims to study the history of Jawi writing and to highlight the extent to which this writing serves as a tool for Islamic knowledge in Malaysia. The research concluded that there is a strong relationship between Jawi writing in the process of Islamic knowledge and language through its contributions to the dissemination of religious sciences to the Malaysian Muslim community and the existence of efforts made by various groups in preserving Jawi writing.